Vpliv števila sodnikov na zanesljivost sodniškega ocenjevanja v standardnih in latinskoameriških plesih - Premelč, Jerneja (Šport (Ljubljana), 2022)
In the last decade, great changes have occurred in judges’ judgement of standard and Latin American dances. Initially, four judging criteria were defined and each of them was rated by three judges. This type of judgement was poorly reliable. In 2017 four judging criteria merged into two components, technical and artistic, and each of them was rated by six judges. The aim of our study was to establish whether the higher number of judges has improved the reliability of their judgement. The sample consisted of 18 Slovenian judges. In all standard and Latin American dances judges rated the 12 best placed adult dancing couples at the Slovenia Open international competition. The results showed that a higher number of judges results in better reliability of their judgement in all four judging criteria. The values of intraclass correlation coefficients (ICC) were higher in the criteria of technical quality and movement to music (ICC = 0.78), whereas those pertaining to partnering skills and choreography were lower (ICC = 0.67; 0.68). The change in the judging system, with introduction of six judges for the rating of each component, has proven to be reasonable and has improved the reliability of judging.
Keywords: latinskoameriški plesi; ocenjevanje; ples; raziskave; sodniki (šport); standardni plesi; šport; športni ples